Economic consumption model revisited: infaq model based on al-Shaybani's levels of al-Kasb - Mohammed, Mustafa Omar (KENMS-IIUM Press, 2011)
This study attempts to investigate the economic ideas of al-Imām MuÍammad Ibn al-×asan al-Shaybānī (1986), focusing on his levels of al-Kasb. The study uses al-Shaybānī’s levels of al-Kasb to develop a theoretical Infāq model that integrates the material, spiritual, moral, social and legal dimensions. Thus the Infāq model is broader than the concept of consumption in modern economics. It also has some advantages over the Islamic consumption models developed by contemporary Muslim economists. The model identifies some major implications in terms of basic needs fulfillment, social Infāq and distributive justice. The primary features of this model are its simplicity and comprehensiveness. It is easy to understand yet it embodies the individual, social, material, spiritual, moral and legal dimensions into the individual’s spending decision making and behavior. The model is more realistic in understanding human behavior. It is growth friendly and instills the spirit of cooperation and social responsibility at the individual and social levels. It is suggested that future research further fine tune with some rigourous analysis JEL Classification: A13, A31, B11, D01, D10 Key words: Al-Kasb, Consumption, Infāq, Model building